Multiscale Features of the Near-Hermean Environment as Derived Through the Hilbert-Huang Transform - Alberti, Tommaso; Milillo, Anna; Laurenza, Monica; Massetti, Stefano; Ivanovski, Stavro L.; Ippolito, Alessandro; Plainaki, Christina; De Angelis, Elisabetta; Mangano, Valeria; Mura, Alessandro; Orsini, Stefano; Rispoli, Rosanna (Frontiers in Physics, 2021)
The interaction between the interplanetary medium and planetary environments gives rise to different phenomena on several temporal and spatial scales. Here we propose, for the first time, the application of the Hilbert-Huang Transform (HHT) to characterize both local and global properties of Mercury’s environment as seen during two MESSENGER flybys. In particular, we compute the energy-time-frequency distribution of the observed magnetic field components and the reconstruction of these signals at large, MHD and kinetic scales through the empirical mode decomposition. We show that the HHT analysis allows to capture and reproduce some interesting features of the Hermean environment as flux transfer events, Kelvin-Helmholtz vortices, and ULF wave activity. Moreover, our findings support the ion kinetic nature of the Hermean plasma structures, the magnetosheath being characterized by anisotropic ion-kinetic intermittent fluctuations, superimposed to both MHD fluctuations and large-scale field structure. Our approach has proven to be very promising for characterizing the structure and dynamics of planetary magnetic field at different scales, for identifying the boundaries, and for discriminating the different scale-dependent features of global and local source processes that can be used for modelling purposes.